New Directions in Private Law Theory - Bettini, Fabiana; Fischer, Martin; Mitchell, Charles; Saprai, Prince (UCL Press, 2023)
New Directions in Private Law Theory brings together some of the best new work on private law theory, reflecting the breadth of this increasingly important field. The contributions interrogate a wide range of topics including aspects of private law doctrine, its development, ordering and application. The authors adopt a variety of different approaches and contribute to ongoing and important debates about the moral foundations of private law, the individuation of areas of private law and the connections between private law and everyday moral experience. Questions addressed include: Does the diversity identified amongst claims in unjust enrichment mean that the category is incoherent? Are claims in tort law always about compensating for wrongs? How should we understand parties' agreement in contract? The contributions shed new light on these and other topics, and the ways in which they intersect and open up new lines of scholarly enquiry. The book will be of interest to researchers working in private law and legal theory, but it will also appeal to those outside of law, most notably researchers with an interest in moral and political philosophy, economics and history.